New insights into global biogeography, population structure and natural selection from the genome of the epipelagic copepod Oithona - Mohammed‐Amin Madoui; Julie Poulain; Kevin Sugier; Marc Wessner; Benjamin Noel; Leo Berline; Karine Labadie; Astrid Cornils; Leocadio Blanco‐Bercial; Lars Stemmann; Jean‐Louis Jamet; Patrick Wincker (Molecular Ecology, 2017)
In the epipelagic ocean, the genus Oithona is considered as one of the most abundant and widespread copepods and plays an important role in the trophic food web. Despite its ecological importance, little is known about Oithona and cyclopoid copepods genomics. Therefore, we sequenced, assembled and annotated the genome of Oithona nana . The comparative genomic analysis integrating available copepod genomes highlighted the expansions of genes related to stress response, cell differentiation and development, including genes coding Lin12‐Notch‐repeat ( LNR ) domain proteins. The Oithona biogeography based on 28S sequences and metagenomic reads from the Tara Oceans expedition showed the presence of O. nana mostly in the Mediterranean Sea ( MS ) and confirmed the amphitropical distribution of Oithona similis . The population genomics analyses of O. nana in the Northern MS , integrating the Tara Oceans metagenomic data and the O. nana genome, led to the identification of genetic structure between populations from the MS basins. Furthermore, 20 loci were found to be under positive selection including four missense and eight synonymous variants, harbouring soft or hard selective sweep patterns. One of the missense variants was localized in the LNR domain of the coding region of a male‐specific gene. The variation in the B‐allele frequency with respect to the MS circulation pattern showed the presence of genomic clines between O. nana and another undefined Oithona species possibly imported through Atlantic waters. This study provides new approaches and results in zooplankton population genomics through the integration of metagenomic and oceanographic data.